Primary Mediastinal Large B-Cell Lymphoma during Pregnancy - Perez, Cesar A.; Amin, Janki; Aguina, Luz M.; Cioffi-Lavina, Maureen; Santos, Edgardo S. (Case Reports in Hematology, 2012)
Non-Hodgkin’s Lymphoma (NHL) rarely presents during pregnancy and primary mediastinal large B-cell lymphoma (PMLBCL) accounts for approximately 2.5% of patients with NHL. The case of a 22-year-old woman who was diagnosed with Stage IIA PMLBCL during week 13 of her intrauterine pregnancy is described. The staging consisted in computed tomography (CT) of the chest and magnetic resonance imaging (MRI) of the abdomen and pelvis. She was managed with R-CHOP regimen (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) for a total of six cycles and, because of the early presentation during the second trimester, she received the entire chemotherapy course during the pregnancy. She delivered a healthy baby at 34 weeks of pregnancy and a 18FDG-PET/CT scan demonstrated complete remission after delivery. After 20 months of follow up she remains with no evidence of disease and her 1-year-old son has shown no developmental delays or physical abnormalities. PMLBCL, although an uncommon subgroup of DLBCL, may present during pregnancy and R-CHOP should be considered as one suitable option in this complex scenario.